Complications as important predictors of disability in ischemic stroke - Pinzon, Rizaldy Taslim; Sanyasi, Rosa De Lima Renita (Faculty of Medicine, Trisakti University, 2017)
BackgroundStroke is the main cause of disability and death in many countries. The high incidence of disability in stroke survivors requires special attention to determine various predictive factors of disability. This study aimed to identify the various predictive factors of disability in ischemic stroke.MethodsThis study was a cross sectional study on 4510 ischemic stroke patients. Each patientâ€™s data had been recorded in the electronic stroke registry of Bethesda Hospital. Ischemic stroke diagnosis was confirmed by brain CT scan, which was interpreted by a neurologist and a radiologist. Disability was assessed using the modified Rankin scale. Predictors of disability were assessed. Multiple logistic regression analysis was used to analyse the data. ResultsThe subjects were predominantly males, >60 years of age, and suffered stroke for the first time. The incidence of disability was 31.5% (1420/4510). Multiple logistic regression analysis showed that the presence of complications (OR: 6.43; 95% CI: 4.74-8.73; p<0.001), decreased level of consciousness (OR: 4.82; 95% CI: 3.95-5.90; p <0.001), onset Â³3 hours (OR: 1.93; 95% CI: 1.52-2.45; p<0.001), recurrent stroke (OR: 1.63; 95% CI: 1.39-1.90; p<0.001), and age >60 years (OR: 1.55; 95% CI: 1.35-1.79; p<0.001) were independent predictive factors of disability.ConclusionWe demonstrated that a substantial proportion of patients with ischemic stroke become disabled. And the presence of complications was the most predictive factor of disability in ischemic stroke.